High-resolution CT scanning of facial trauma. - Cooper, P W; Kassel, E E; Gruss, J S (American Journal of Neuroradiology, 1983)
Computed tomographic (CT) scanning offers a simple, fast, and accurate study of complex maxillofacial trauma especially in the patient with multiple injuries. At the time of CT brain scanning, the facial bones can be scanned with only minimal extra time. High-resolution scanning provides excellent bony detail equal to or better than complex-motion tomography with the advantage of better contrast resolution as well. Application of craniofacial surgical techniques is facilitated by the accurate display of the nature and extent of fracturing. Surgical findings of extent of fracturing correlate better with high-resolution scanning than with plain films and conventional tomography.